Direct effect of dsRNA mimetics on cancer cells induces endogenous IFN-β production capable of improving dendritic cell function - Gatti, Gerardo Alberto (2013)
Viral double-stranded RNA (dsRNA) mimetics have been explored in cancer immunotherapy to promote antitumoral immune response. Polyinosine–polycytidylic acid (poly I:C) and polyadenylic–polyuridylic acid (poly A:U) are synthetic analogs of viral dsRNA and strong inducers of type I interferon (IFN). We describe here a novel effect of dsRNA analogs on cancer cells: besides their potential to induce cancer cell apoptosis through an IFN-β autocrine loop, dsRNA-elicited IFN-β production improves dendritic cell (DC) functionality. Human A549 lung and DU145 prostate carcinoma cells significantly responded to poly I:C stimulation, producing IFN-β at levels that were capable of activating STAT1 and enhancing CXCL10, CD40, and CD86 expression on human monocyte-derived DCs. IFN-β produced by poly I:C-activated human cancer cells increased the capacity of monocyte-derived DCs to stimulate IFN-γ production in an allogeneic stimulatory culture in vitro. When melanoma murine B16 cells were stimulated in vitro with poly A:U and then inoculated into TLR3−/− mice, smaller tumors were elicited. This tumor growth inhibition was abrogated in IFNAR1−/− mice. Thus, dsRNA compounds are effective adjuvants not only because they activate DCs and promote strong adaptive immunity, but also because they can directly act on cancer cells to induce endogenous IFN-β production and contribute to the antitumoral response.